The Effect of the Convenience and Benefits of GoPayLater on the Interest in Use with Moderation of Trust among FEB UNJ Students - Mardiana Saharani; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The development of digital technology in the financial sector has encouraged the emergence of non-cash payment services, one of which is paylater. GoPayLater is a paylater service that is widely used by students because it offers convenience and flexibility in payments. The purpose of this study is to examine the effect of usability and its advantages on the interest in using GoPayLater, considering trust as a variable that intervenes, among Jakarta State University's Faculty of Economics and Business students. Quantitative techniques are employed, implementing an explanatory design. A Likert scale was used to gather the data questionnaire, administered to students via Purposive sampling is used by GoPayLater. Data analysis is done using partial least squares-structural equation modeling (PLS-SEM). The results shown that interest and trust in use were significantly impacted by usability. On the other hand, the benefits of use are significantly influenced by usage interest but not by trust. In addition, trust has no significant effect on usage interest. These findings show that the functional aspect is the main factor in encouraging interest in using GoPayLater among students.